1999
DOI: 10.1046/j.1460-9592.1999.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two concentrations of bupivacaine and adrenaline with and without fentanyl in paediatric inguinal herniorrhaphy

Abstract: This study was designed to determine whether administration of caudal bupivacaine with fentanyl would have any effect on analgesia in paediatric patients undergoing inguinal herniorrhaphy repair. Fifty-six outpatient paediatric patients undergoing inguinal hernia repair were evaluated. Patients received, in a randomized manner, 1 ml.kg-1 of either bupivacaine 0.25% or 0.125% with or without fentanyl 1 microg.kg-1. There was no difference in pain scores in the hospital, the night of surgery, or 24 h postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Joshi et al . (10) found that there were no differences between caudal 1 ml·kg −1 bupivacaine 0.25% and 0.125% with or without fentanyl 1 µg·kg −1 in pain scores or analgesic requirement in patients who underwent inguinal hernia repair. Campbell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Joshi et al . (10) found that there were no differences between caudal 1 ml·kg −1 bupivacaine 0.25% and 0.125% with or without fentanyl 1 µg·kg −1 in pain scores or analgesic requirement in patients who underwent inguinal hernia repair. Campbell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ropivacaine has become the agent of choice in paediatric epidural analgesia due to the lower incidence of cardiotoxicity and central nervous system toxicity 2 . Adjuvant opioids to local anaesthetics have been studied to allow better analgesia without increasing the incidence of adverse effects with varying results 1–3,7,8 . The effective concentration of ropivacaine for caudal analgesia ranges from 1.3 to 2.0 mg/ml when ropivacaine was used alone 9–12 .…”
Section: Discussionmentioning
confidence: 99%
“…The dose of bupivacaine in our study was 0.25% (1mL/kg) regarding the caudal blocks. A comparison between the 0.25% and 0.125% caudal bupivacaine on 56 outpatient paediatric patients undergoing inguinal hernia repair, showed that the 0.25% bupivacaine was related with a higher incidence of vomiting at home, irrespective of the use of fentanyl (19).…”
Section: Discussionmentioning
confidence: 99%